Pemanfaatan Ekstrak Daun Pepaya (Carica papaya. L) dan Madu sebagai Peningkatan Nafsu Makan pada Anak di Kelurahan Sukorame Kec. Mojoroto Kabupaten Kediri Jawa Timur - Herman Herman; Okky Intan Mawarni; Fendy Prasetyawan; Mohammad Firdaus Alshol; Prayoga F. Yuniarto (Jurnal Pengabdian Masyarakat, 2026)
Background: Children often face problems with appetite, which can affect their growth and overall health, making safe and natural solutions necessary, such as the use of papaya leaf extract (Carica papaya L.) and honey. Objective: This community service program was conducted in Sukorame Village, Mojoroto District, Kediri Regency, through counseling and training for parents on the benefits and administration of papaya leaf extract and honey to improve children’s appetite. Method: The implementation method included coordination with partners, preparation of materials and tools, and direct demonstration-based education. Result: Results showed an increase in parents’ knowledge from an average score of 52.6 to 87.8 (±82%), the frequency of children eating ≥3 times/day increased from 36% to 72%, portion sizes improved in 68% of children, and the average body weight increased by 0.4 kg within 14 days of intervention. A total of 48% of children experienced significant improvements across all indicators (meal frequency, portion size, and body weight). These findings indicate that the combination of papaya leaf extract and honey effectively enhances children’s appetite through improved digestion and natural energy provision, offering a safe and affordable alternative to improve child nutrition.